Erythrodermic psoriasis and severe hypotension requiring intensive care unit hospitalization: Poor treatment outcome as a result of poor adherence. (3rd March 2016) - Vaidya, Toral S.; Lewallen, Robin S.; Feldman, Steven R.
Abstract: Psoriasis is closely associated with cardiovascular comorbidities. Poor adherence can affect both psoriasis outcomes and the effectiveness of treatment for cardiovascular comorbidities. We discuss a case of psoriasis medication nonadherence resulting in admission to the dermatology inpatient service for erythrodermic psoriasis. Administration of the patient's prescribed home antihypertensive regimen on admission resulted in a severe hypotension requiring transfer to the medical intensive care unit (ICU). This case illustrates the role of poor adherence in an erythrodermic flare of psoriasis; this case also illustrates how new-onset regimented adherence, in a formerly nonadherent patient, may result in life-threatening iatrogenic disease.